Um estudo das práticas de disseminação de informação de contratos administrativos nos portais eletrônicos das universidades federais da região sudeste - Santos, Lincoln Kennedy dos (Universidade Federal de São Carlos, 2018)
Social participation is fundamental to the control of state action, ensuring transparency to acts of Public Administration. Fiscal transparency is established for in Complementary Law 101/2000, ensuring transparency as a mean of control and inspection. The 12.527/2011 Law institutes as a fundamental principle that access to public information is the rule and secrecy the exception. Due to the importance of this theme, considering that currently the sharing of information occurs through the internet, this research aims to clarify the dissemination practices of information on administrative contracts in the portals of the federal universities of the Southeast region, which promote the strengthening of participation of the citizen and community. It seeks practices that go beyond the legal requirement, highlighting the best characteristics that portals must present for the availability and access to administrative contracts, emphasizing the importance of the availability of complementary information relating to contracts required for comparisons and various analyzes. In this exploratory and descriptive research, the content analysis method with the creation of a form for data collection is used to increase the possibility of discoveries during the research. The public administration is contextualized by means of theoretical reference, focusing on publicity and transparency of administrative contracts, on the structure of government portals and the availability of information relating to administrative contracts. The laws relating to administrative contracts, fiscal responsibility, corruption against public administration and access to information are presented. The results provide a scenario of how publicity of information on administrative contracts is being done in the portals of the studied universities, allowing the possibility of improvement in the method of availability and access of this information. Finally, in this process of public management, information management and public transparency, despite advances in the intention of transparency of public acts, it is understood that much must be done for efficiency to be achieved. It is considered fundamentally, as defined by the Access to Information Law, 12,527/2011 Law, that the Public Administration has to be proactive in availability of information regardless of requests.
A study of the dissemination practices of information of administrative contracts in the electronic portals of the federal universities of the Southeast region
Keywords: Transparência pública; Contrato administrativo; Fiscalização; Accountability; Public transparency; Administrative contract; Supervision; Accountability; Supervisión; Rendición de cuentas; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS